Using Google Docs in German as Foreign Language Writing Course during the Covid-19 Pandemic - Dani Hendra (Future Science)
Writing and speaking are related. Of the four language skills, there are two productive skills, namely writing and speaking. Learning to write takes a lot of time and can therefore lead to ineffective teaching in the classroom. Self-study outside of class would be a possible solution so that students could always practice their language skills and apply what they have learned. In this pandemic, where learning is only possible online, an application is needed to replace the activities done in the face-to-face phase. These activities can be done anywhere as long as there is an internet connection. The internet is no stranger to the students themselves. They grew up with it at the time, so it should be easy to deal with. Technology is currently developing at a rapid pace. Technological developments create new applications that are useful in the classroom. The search engine, google, provides many applications through which interaction among students or between students and lecturers could take place. One of the applications present in google is google docs. The students do the writing tasks on google docs. Not only can the tasks be found on google docs, but the comments and suggestions for improvement can also be read here. This encourages students to actively participate. This letter shows how the students interact, what mistakes the students make when writing and how they correct it themselves.